Optimasi Suhu Reboiler pada De-Butanizer Column untuk Meningkatkan Efisiensi Energi dan Menjaga Kualitas LPG Mixed - Herani, Lingga Putri; Ripaldi, Alif; Cundari, Lia; Muhammad Ardian; Januari, Ristian (Jurnal Ilmiah Teknik Kimia, 2026)
The fractionation plant of PT Perta-Samtan Gas Sungai Gerong separates hydrocarbon components from Natural Gas Liquid (NGL) into Liquefied Petroleum Gas (LPG) products that comply with the specifications of SK Ditjen Migas No. 116.K/10/DJM/2020. One key unit in this process is the De-Butanizer Column, which separates butane from lighter fractions. This study analyzes the effect of reboiler temperature variation on the composition of the LPG mixed and on energy efficiency in the distillation system. The simulation was performed in Aspen HYSYS V.14 using the Peng–Robinson equation of state and was based on actual operating data from the plant’s Distributed Control System (DCS). The results show that decreasing the reboiler temperature increases the propane (C3) content while reducing butane (C4) in the LPG mixed, with some butane carried over to the bottom product due to a lower boil-up rate. The optimal condition was found at 279.1 °F: at this temperature the LPG mixed still met quality standards while heat-flow consumption decreased by 460,491.74 kJ/h, resulting in annual energy savings of approximately Rp 321,073,593.25. This analysis concludes that operating the reboiler at a lower temperature can enhance energy efficiency without compromising product quality, thereby offering significant economic benefits to the company.